Content Marketing, Live Streaming, And Online Customer Reviews On Fashion Product Purchase Decisions - Agam Misbakhudin; Nurul Komaryatin (Iqtishaduna: Jurnal Ilmiah Ekonomi Kita, 2023)
This research analyzes the influence of content marketing, live streaming, and online customer reviews on purchasing decisions for Shopee fashion products. This type of research is explanatory research with a quantitative approach. The population in this research is all consumers who have purchased fashion products at Shopee in the Jepara area. The data source used is primary data from distributed questionnaires. Samples were taken using the simple random sampling method with Lameshow measurements, obtaining a sample of 100 people. The data analysis technique used in this research is multiple linear regression analysis using SPSS version 23 statistical tools. The research results show that content marketing positively influences fashion product purchasing decisions. Live streaming positively influences fashion product purchasing decisions. Online customer reviews positively influence fashion product purchasing decisions. This research can provide in-depth insight into the factors influencing consumer purchasing decisions on the Shopee platform, especially fashion products. These findings can be an essential reference for business people, marketers, and researchers to develop more effective marketing strategies in the e-commerce context.